Viewing speech modulates activity in the left SI mouth cortex. - Möttönen, R; Järveläinen, J; Sams, M; Hari, R (2005)
The ability to internally simulate other persons' actions is important for social interaction. In monkeys, neurons in the premotor cortex are activated both when the monkey performs mouth or hand actions and when it views or listens to actions made by others. Neuronal circuits with similar "mirror-neuron" properties probably exist in the human Broca's area and primary motor cortex. Viewing other person's hand actions also modulates activity in the primary somatosensory cortex SI, suggesting that the SI cortex is related to the human mirror-neuron system. To study the selectivity of the SI activation during action viewing, we stimulated the lower lip (with tactile pulses) and the median nerves (with electric pulses) in eight subjects to activate their SI mouth and hand cortices while the subjects either rested, listened to other person's speech, viewed her articulatory gestures, or executed mouth movements. The 55-ms SI responses to lip stimuli were enhanced by 16% (P<0.01) in the left hemisphere during speech viewing whereas listening to speech did not modulate these responses. The 35-ms responses to median-nerve stimulation remained stable during speech viewing and listening. Own mouth movements suppressed responses to lip stimuli bilaterally by 74% (P<0.001), without any effect on responses to median-nerve stimuli. Our findings show that viewing another person's articulatory gestures activates the left SI cortex in a somatotopic manner. The results provide further evidence for the view that SI is involved in "mirroring" of other persons' actions.